APLIKASI GAME BALL “Bola” BERBASIS ANDROID - Christine, Christine; Pragantha, Jeanny; Haris, Darius Andana (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
In this game, players are asked to drop the ball onto the board. There are 2 modes in this game, namely one hand and two hands. There are 10 different stages for each mode. This game uses a multitouch feature. Stages 2 to 10 have minimum points to be able to open and play the next stage. This game has been tested using the black box method, alpha testing and beta testing using questionnaires via Google Form and Google drive to store Bola game files. The test results show that Bola is interesting to play repeatedly, the gameplay features can be easily understood, and the design is attractive.